Thyroxine-induced induction of pyroglutamyl peptidase II and inhibition of TSH release precedes suppression of TRH mRNA and requires type 2 deiodinase - Marsili, Alessandro (2011)
Suppression of TSH release from the hypothyroid thyrotrophs is one of the most rapid effects of T3 or T4. It is initiated within an hour, and precedes the decrease in TSHβ mRNA inhibition and is blocked by inhibitors of mRNA or protein synthesis. TSH elevation in primary hypothyroidism requires both the loss of feedback inhibition by thyroid hormone in the thyrotrophs and the positive effects of TRH. Another event in this feed back regulation may be the thyroid hormone induction of the TRH-inactivating pyroglutamyl peptidase II (PPII) in the hypothalamic tanycytes. This study compared the chronology of the acute effects of T3 or T4 on TSH suppression, TRH mRNA in the hypothalamic paraventricular nucleus (PVN), and the induction of tanycyte PPII. In wild type mice, T3 or T4 caused a 50% decrease in serum TSH in hypothyroid mice by 5 hours. There was no change in TRH mRNA in PVN over this interval, but there was a significant increase in PPII mRNA in the tanycytes. In mice with genetic inactivation of the type 2 iodothyronine deiodinase, T3 decreased serum TSH and increased PPII mRNA levels, while T4-treatment was ineffective. We conclude that the rapid suppression of TSH in the hypothyroid mouse by T3 occurs prior to a decrease in TRH mRNA though TRH inactivation may be occurring in the median eminence through the rapid induction of tanycyte PPII. The effect of T4, but not T3, requires the type 2 iodothyronine deiodinase.